Gene therapy targeting haematopoietic stem cells for inherited diseases: progress and challenges - Cavazzana, Marina; Bushman, Frederic D.; Miccio, Annarita; André-Schmutz, Isabelle; Six, Emmanuelle (Nature reviews. Drug discovery, 2019)
Pioneering gene therapy trials have shown that the genetic engineering of haematopoietic stem and progenitor cells can be an alternative to allogeneic transplantation in the treatment of primary immunodeficiencies. Early trials also highlighted the risk of insertional mutagenesis and oncogene transactivation associated with the first generation of gammaretroviral vectors. These events prompted the development of safer, self-inactivating lentiviral or gammaretroviral vectors. These lentiviral vectors have been successfully used to treat over 200 patients with 10 different haematological disorders (including primary immunodeficiencies, haemoglobinopathies and metabolic disorders) and for the generation of chimeric antigen receptor-T cells for cancer therapy. However, several challenges, such as effective reconstitution during inflammation, remain if gene therapy is to be extended to more complex diseases in which haematopoietic stem and progenitor cells can be altered by the disease environment. We discuss the progress made and future challenges for gene therapy and contrast gene therapy with gene-editing strategies. Advances in the design of vectors based on retroviruses, such as lentiviruses and gammaretroviruses, have led to improvements in the safety and stability of gene therapies directed at haematopoietic stem and progenitor cells. In this Review, Cavazzana and colleagues discuss the results from recent clinical trials of retroviral vectors for the treatment of genetic disorders, including severe combined immunodeficiencies and β-haemoglobinopathies (β-thalassaemia and sickle cell disease). They highlight the progress made and the remaining challenges in applying gene therapies more broadly.